Hybrid photocatalytic–microbial fuel cells systems: Progress, challenges, and forecasts in water-energy-environment nexus - Hussain, Rabia Tasaduq; Anandapadmanaban, Baala H.; Lin, Chi-Wen; Liu, Shu-Hui; Jun Haslinda, Shariffuddin (Elsevier Ltd, 2026)
The growing demand for sustainable water purification and renewable energy recovery has propelled hybrid photocatalytic–microbial fuel cell (photo−MFC) systems to the forefront of environmental engineering. These coupled configurations merge semiconductor-driven redox reactions with bioelectrochemical energy conversion, creating a self-sustaining process that simultaneously degrades pollutants and generates electricity. This review critically discusses the advances, mechanisms, types, and design innovations in hybrid photo-MFC systems, with a particular emphasis on charge-transfer pathways, the physicochemical compatibility between photocatalysts, electrodes, and electroactive biofilms, and the influence of reactor architecture on system performance. Studies on key advances in visible-light-responsive semiconductors, nanostructured electrodes, and integrated reactor architectures increasing photon utilization and e− recovery are analysed. Current challenges related to power density, catalyst durability, biofouling, and scalability are identified. The paper concludes with a future perspective on emerging trends such as 3D-printed biochar photoelectrodes, machine-learning-guided reactor optimization, and techno-economic evaluations needed for industrial-level development. By integrating insights from diverse interdisciplinary fields, this review outlines strategic pathways for advancing hybrid photo−MFC technologies towards the circular and energy-positive treatment of wastewater.